Designing anti-wear surfaces on Ti64 alloy: Influence of surface texturing and RF sputtered Ti/TaN coatings - Pavan Kumar Vangara; Turali Narayana; Raghuveer Dontikurti; Gaurav Pant; Sunil Kumar Tiwari; Durgaprasad Kelli; Santhosh Kumar Dubba; Shahid Saleem (Next Materials, 2025)
This study investigates the use of laser surface texturing and RF magnetron sputtering to deposit Ti/TaN nanostructured coatings on Ti-6Al-4V (Ti64) alloy for enhanced mechanical and tribological properties. Three types of samples were examined: bare substrate (SS), Ti/TaN-coated surface, and coating on textured surface (CTS). Surface characterization was performed using GIXRD, FESEM, EDS, Raman spectroscopy, 3D profilometry, and nanoindentation. The Ti/TaN coatings, with a ∼100 nm Ti interlayer and ∼410 nm TaN top layer, exhibited a dense and uniform structure with good adhesion. This improved the hardness from 6.08 GPa (bare) to 23.57 GPa (Ti/TaN), a 288 % increase. Tribological tests using a ball-on-disc tribometer with Si3N4 counter body under 1 N load showed notable improvements. The Ti/TaN coating reduced the coefficient of friction by 36.7 % and the wear rate by 82.1 % compared to the bare sample. The CTS surface performed even better, with reductions of 53.1 % in friction and 84.8 % in wear. These results demonstrate the synergistic effect of Ti/TaN coatings and surface texturing in enhancing the properties of Ti64 alloy for biomedical applications.